1996
DOI: 10.1177/030098589603300606
|View full text |Cite
|
Sign up to set email alerts
|

Hydranencephaly, Cerebellar Hypoplasia, and Myopathy in Chick Embryos Infected with Aino Virus

Abstract: Abstract. Pathogenesis of Aino virus (AIV), a suspected causative agent of congenital abnormalities of calves,has not yet been established by experimental infection of dams. To investigate the pathogenesis, lo3 median tissue culture infective doses per 0.2 ml of AIV strain JaNAr 28 was inoculated into the yolk sac of 8-day-old chick embryos. At 4, 7, 10, and 13 days post-inoculation (PI) 20 eggs were opened and macro-and microscopic studies combined with virus recovery and immunohistochemical detection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…From experimental infection studies with Akabane and Aino virus, using chick embryos 19,20,25 or primary cultures of fetal bovine brain, 18 it is known that these viruses preferentially infect neuronal and astroglial cells. Interestingly, vascular wall thickening in brain tissue was seen to be associated with necrotizing encephalitis in chickens at 7 days postinfection to form granulomatous lesions at 10 and 13 days postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…From experimental infection studies with Akabane and Aino virus, using chick embryos 19,20,25 or primary cultures of fetal bovine brain, 18 it is known that these viruses preferentially infect neuronal and astroglial cells. Interestingly, vascular wall thickening in brain tissue was seen to be associated with necrotizing encephalitis in chickens at 7 days postinfection to form granulomatous lesions at 10 and 13 days postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Although serologic data suggested that AINOV caused congenital abnormalities of cattle and sheep in Japan and Australia [1,12], the pathogenicity of AINOV in cattle has not been demonstrated. Viral teratogenicity in cattle and sheep has been well demonstrated for AKAV [2,8,11,13], a member of bunyavirus; however, the teratogenicity of AINOV has been examined only in chick embryos [5][6][7]. To determine the role of AINOV in inducing congenital malformation, fetal cattle were exposed to maternal and direct routes of infection with the virus and examined for transplacental activity of the virus and developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed that AINOV was equally teratogenic for cattle as AKAV. It has been shown that chick embryos manifest marked hydranencephaly, cerebellar hypoplasia, arthrogryposis and scoliosis by inoculation into the yolk sac of eight days embryo with AINOV [5][6][7]. Kitano et al [6] mentioned that cerebellar hypoplasia in AINOV-infected chick embryos constitutes a distinctive difference from AKAV-infected chick embryos, which showed hydranencephaly and myopathy [9].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of cerebellar hypoplasia in neonatal animals is an intrauterine viral infection during early or midgestation. A number of different viruses are capable of causing this malformation, including herpes simplex virus, 13 bluetongue virus, 14 Chuzan virus, 15 Akabane virus, 16 rift valley fever virus, 17 Cache Valley and Aino viruses, 4,17 the pestiviruses of bovine virus diarrhea (BVD) and hog cholera, 1,2 the flavivirus of Wesselbron disease, 17 Rubella, and the parvovirus of feline panleukopenia. 18 Cerebellar hypoplasia has been recognized in cats as early as 1888.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections occur most commonly in cats and cattle but have been described in sheep, pigs, goats, and chickens. [1][2][3][4][5] Cerebellar hypoplasia has not been described in the dog secondary to in utero viral infection. Congenital cerebellar malformations are reported occasionally in dogs, and typical lesions include partial or complete absence of the cerebellar vermis.…”
mentioning
confidence: 99%